Pengelolaan Komposter untuk Anak Usia Dini: Mengubah Kesadaran Lingkungan dan Pengurangan Sampah - Anggraeni, Ira (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2024)
This study investigates the impact of composter management practices on the environmental awareness and behavior of young children about waste reduction. This research included observations, interviews, and the direct participation of children to identify the changes in their understanding of recycling organic waste into compost, which is beneficial for plants. The research findings indicate that children actively participate in substantial conversations regarding the composting process and recognize the vital role of organic waste management for the environment. This study emphasizes the importance of teachers in guiding children to identify and comprehend the distinctions between organic and inorganic waste by focusing on the process of managing composters. Children's active involvement in managing composters leads to behavioral changes such as enhanced awareness of the waste recycling process, commitment to environmental sustainability, and engagement in practical efforts to reduce landfill waste.